The impact of teaching mathematics using the Desmos program on the achievement of students of the Faculty of basic education (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the impact of teaching mathematics using the Desmos program on the achievement of students of the Faculty of basic education . The research sample was deliberately selected from the first-stage students in the Department of computers /Faculty of basic education, and consisted of (62) students with (31) students in each of the experimental and control research groups.the two groups were rewarded in the variables "intelligence, chronological age, previous achievement in mathematics, educational level of parents" and the experiment was applied in the first course of the academic year (2023/2024). The research tool was prepared, namely: the achievement test in the differential subject and consisted of (30) paragraphs, of which (26) objective paragraphs of the multiple choice type and(4) essay paragraphs, and using the equation (Alpha cronbach) the value of the coefficient of constancy was (0.98). After the completion of the experiment, the achievement test in the differential subject was applied to the two research groups and after collecting the data and using the appropriate statistical means, the results showed the superiority of the students of the experimental group who studied the material using the Desmos program over the students of the control group who studied the same material in the usual way. In light of the research results, the researcher recommended encouraging university teachers to use interactive computing programs in teaching, including the Desmos program, and suggested conducting a study of the effectiveness of teaching mathematics using the Desmos program with other dependent variables such as creative thinking, engineering thinking, and multiple intelligences .